VARIAÇÕES INTERESPECÍFICAS DO PERFIL QUÍMICO DO VENENO DE VESPAS POLISTINAE (HYMENOPTERA, VESPIDAE) POR FTIR-PAS - SGUARIZI-ANTONIO, Denise; MICHELUTTI, Kamylla Balbuena; SOARES, Eva Ramona Pereira; MENDONÇA, Angélica; TORRES, Viviana de Oliveira; ANTONIALLI-JUNIOR, William Fernando (ANAIS DO ENIC, 2017)
-